COVID-19 bringing cairenes back to their streets - Salma Ghanem; Aliaa F. Ahmad; Sarah Aboualy (Journal of Urban Management, 2021)
In a city of high vehicular traffic like Cairo, in some neighborhoods simple social activities were usually practiced in enclosed places. The outbreak of the Covid-19 pandemic has somehow turned the corner in the street life of Cairo as the livability of the urban public spaces enhanced. Residents of Cairo were widely seen using every well-maintained public space they could find. This paper aims to explore the emerging questions concerning Covid-19 and its effect on the city. How did Covid-19 help in bringing residents of Cairo back to the streets? What kind of street activities were introduced during the pandemic and what are the reasons behind them? What are the effects of these novel activities on both the people and the city? Basing on relevant international literature, this research will provide a comparative analysis between urban public life in the streets of Cairo before and during the pandemic. The research adopts a case study qualitative approach for a selected neighborhood in Cairo. It relies on observations, focus group discussions and in-depth interviews with residents from the district. Findings indicate that enclosed commercial and recreational facilities, and vehicular domination in the streets have taken life away from the city before the lockdown period. During the pandemic people have acquired new habits which gave life back to the streets. The flow of the main social stream has a very important role in shaping the street life. As a result of these new circumstances the physical and psychological health of the residents were maintained, new social ties were created and their sense of belonging has been enhanced.
Keywords: 710; Cairo; Urban life; Public spaces; Covid; 19